2012
DOI: 10.1155/2012/418650
|View full text |Cite
|
Sign up to set email alerts
|

Dissection and Exposure of the Whole Course of Deep Nerves in Human Head Specimens after Decalcification

Abstract: The whole course of the chorda tympani nerve, nerve of pterygoid canal, and facial nerves and their relationships with surrounding structures are complex. After reviewing the literature, it was found that details of the whole course of these deep nerves are rarely reported and specimens displaying these nerves are rarely seen in the dissecting room, anatomical museum, or atlases. Dissections were performed on 16 decalcified human head specimens, exposing the chorda tympani and the nerve connection between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… Diagram of the course of the intratemporal facial nerve from the fundus of the IAC to the stylomastoid foramen [10]. …”
Section: Figurementioning
confidence: 99%
“… Diagram of the course of the intratemporal facial nerve from the fundus of the IAC to the stylomastoid foramen [10]. …”
Section: Figurementioning
confidence: 99%
“…Măru et al (19) found the CF-SM length went from 0.2 to 9.7 mm with a mean of 7.2 mm. On the other hand, CF-SM length ranged from 5.93 to 21.63 mm with a mean of 13.32 in the study of Liu et al (20) The CF-SM length ranged from 2.06 to 5.5 mm with a mean of 4.08 ± 0.8 mm in the study of Jain et al (21) on 35 temporal bones.…”
Section: Discussionmentioning
confidence: 94%
“…14 Liu et al described chorda tympani as a very fine nerve (0.44 mm in diameter within the tympanic cavity), and the distance between the chorda tympani and stylomastoid foramen as ranging from 5.93 mm to 21.63 mm, with the average distance being 13.32 mm. 13 Zou et al found the distance from the crotch of the CTN to the stylomastoid foramen to be 2.67 +/− 0.51 mm. 24…”
Section: Discussionmentioning
confidence: 99%
“…There is lot of variability in the origin of the chorda tympani above stylomastoid foramen. 13 14 15 Hence, the CTN is potentially vulnerable in all CI surgeries. Unfavorable anatomy of the FN also places the FN at risk.…”
Section: Introductionmentioning
confidence: 99%